Hemagglutinating Property of Haemophilus aegyptius - Mann, Jerry M. (1968)
Extracts possessing the capacity to hemagglutinate normal human erythrocytes were recovered from Haemophilus aegyptius by treatment with either diethylene glycol or acetone. Antisera prepared against these extracts or the unextracted bacterial cell inhibited hemagglutination by homologous and heterologous antigens. Microgel diffusions indicated the presence of identical components in each extract as expressed by lines of identity between antisera to each fraction. The hemagglutinin was identified as a lipopolysaccharide, 42% lipid and 57% carbohydrate. The determination of 6% phosphorus in the lipid fraction identified it as containing phospholipid.